2018
DOI: 10.1007/s10653-018-0143-7
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity effects and biomarkers of tebufenozide exposure in Yuukianura szeptyckii (Collembola: Neanuridae)

Abstract: Tebufenozide is an insect growth regulator used to control pest caterpillar populations. As an ecdysone agonist, tebufenozide is equally toxic to several non-target arthropod species, binding the receptor sites of the molting hormone 20-hydroxyecdysone and causing premature and lethal molting. In this study, the toxic effects of tebufenozide were assessed, and biomarkers of tebufenozide exposure were identified, in the non-target soil collembolan species Yuukianura szeptyckii. Adult mortality and reproduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…In evaluating the risks of pesticides, identifying the effects of pesticides on organisms at the sub-individual level is important because pesticides may not only affect the survival or reproduction of organisms, but also impair the ecological fitness of individuals through sublethal effects [25,26,28]. Our study using fatty acids as a biomarker confirmed that A. kimi can be biochemically affected by glyphosate treatment even at the concentrations at which no glyphosate-induced adult mortality and juvenile reproduction were observed (Figure 2 and Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In evaluating the risks of pesticides, identifying the effects of pesticides on organisms at the sub-individual level is important because pesticides may not only affect the survival or reproduction of organisms, but also impair the ecological fitness of individuals through sublethal effects [25,26,28]. Our study using fatty acids as a biomarker confirmed that A. kimi can be biochemically affected by glyphosate treatment even at the concentrations at which no glyphosate-induced adult mortality and juvenile reproduction were observed (Figure 2 and Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Biomarker-based approaches have been extensively applied to assess these sub-individual effects [25,26]. Enzyme activity [27], protein composition [28], and gene expression [29] have been mainly used as toxicity biomarkers for soil animals. In addition to these biomarkers, fatty acids are also considered potentially important biomarkers, because they are essential components of organisms and play a critical role in energy storage, cell structure, and regulatory physiology [30].…”
Section: Introductionmentioning
confidence: 99%
“…Proteins related to glycolysis can be affected by low doses (e.g., <NOEC for reproduction of 43.8 mg a.i. kg À1 d.w.) of tebufenozide in the collembolan Yuukianura szeptyckii [93]. Neonicotinoids can induce gene downregulation in the brain of honey bee workers, namely, those encoding the enzymes related to glycolysis and lipids.…”
Section: Effect Of Insecticides At Sub-organism Levelmentioning
confidence: 99%
“…Body weight of P. scaber was not affected by chlorantraniliprole [104], but it was significantly lower in the presence of thiacloprid [105]. The molting frequency of Y. szeptyckii was affected by tebufenozide [93]. Yu et al [114] reported no effects of imidacloprid on the development time, pupation, and adult emergence of the ladybug Coccinella septempunctata, while egg production and hatching were compromised.…”
Section: Effects Of Insecticides At Individual and Population Levelsmentioning
confidence: 99%
“…As an ecdysone inhibitor, it has a specific insecticidal mechanism: tebufenozide mimics the function of natural insect ecdysone, interacts with the ecdysone receptor protein, induces early maturity of insects, and causes insects to moult to death. As a third‐generation insect growth regulator, tebufenozide was developed to replace traditional pesticides and to reduce environmental and food contamination . Due to its unique insecticidal mechanism and high selectivity, it is safe and reliable for the environment and non‐target organisms.…”
Section: Introductionmentioning
confidence: 99%